User Generated Content pada Tiktok dan Penggunaannya di Kalangan Muda - Gautama, Vivin Arbianti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
User Generated Content is an activity from users of a platform in producing content and then sharing it on that platform. User Generated Content is used by users to share information, promote a brand and even influence it for the purpose of increasing purchases. Along with the development of social media such as Facebook, Instagram, Twitter, Youtube and Linked In. These social media have their own uniqueness and are liked by users with different goals and characteristics. TikTok is the fastest growing platform that young people love because it is a short video format that can be combined with music and is easy to create. This study aims to review the use of User Generated Content concept and its use in applications especially the TikTok application based on article published in several journal, using the literature review method. The result is shown some article journal have studied that User Generated Content used on social media platforms could increase purchase intentions in addition to its function of communicating or informing content. Some articles in journal claimed that User Generated Content on the TikTok platform is used by young people as entertainment and relaxation as well as to share educational and science content.